Graphene-based nanomaterials for stimuli-sensitive controlled delivery of therapeutic molecules - Khakpour, Elnaz; Salehi, Saba; Naghib, Seyed Morteza; Ghorbanzadeh, Sadegh; Zhang, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
Stimuli-responsive drug delivery has attracted tremendous attention in the past decades. It provides a spatial- and temporal-controlled release in response to different triggers, thus enabling highly efficient drug delivery and minimizing drug side effects. Graphene-based nanomaterials have been broadly explored, and they show great potential in smart drug delivery due to their stimuli-responsive behavior and high loading capacity for an extended range of drug molecules. These characteristics are a result of high surface area, mechanical stability and chemical stability, and excellent optical, electrical, and thermal properties. Their great and infinite functionalization potential also allows them to be integrated into several types of polymers, macromolecules, or other nanoparticles, leading to the fabrication of novel nanocarriers with enhanced biocompatibility and trigger-sensitive properties. Thus, numerous studies have been dedicated to graphene modification and functionalization. In the current review, we introduce graphene derivatives and different graphene-based nanomaterials utilized in drug delivery and discuss the most important advances in their functionalization and modification. Also, their potential and progress in an intelligent drug release in response to different types of stimuli either endogenous (pH, redox conditions, and reactive oxygen species (ROS)) or exogenous (temperature, near-infrared (NIR) radiation, and electric field) will be debated.